"Looking After Yourself Is Self-Respect": The Limits and Possibilities of Men's Care on a Night Out. (March 2022) - Duncan, Tristan; Roberts, Steven; Elliott, Karla; Ralph, Brittany; Savic, Michael; Robards, Brady
Notions of masculinity have played a central role in social and cultural research on men's drinking events. Within this context, masculinity is regularly called on to explain the problematic disparities that mark men's alcohol consumption, including men's disproportionate involvement in drinking and a range of alcohol-related harms. More recently, however, researchers have begun to emphasize men's drinking events as sites of care and support, leading some to suggest that men's drinking masculinities are evolving in affirmative and health promoting ways. While unsettling the tendency of scholars to problematize men's drinking masculinities, foregrounding the possibilities of men's care potentially obscures its complexities and constraints. In this paper, we are concerned to critically re-examine the relationship between masculinity, care, and events of men's alcohol consumption. Where some authors have positioned men's care as an innate or uncomplicated good, we draw on a feminist ethics of care approach to explore its complexities, constraints, and exclusions. Through focus group discussions with 101 men, our analysis describes how ideals of masculine autonomy emerged through men's accounts of drinking events, fundamentally shaping the constitution, practice, and possibilities of care. For the men in our study, the valorization of autonomy fostered ambivalence and tension around care, hindering their capacity as care givers and receivers. In turn, opportunities and accountability for care were overlooked, avoided, or displaced onto women. By highlighting the complexity of men's care, our account complicates existing scholarship on men's drinking while also gesturing toward new avenues for public health practice. We conclude by outlining how a more concerted focus on care may be integrated into public health policy, research, and programming and, in the process, contribute to the promotion of more health affirming and ethical modes of masculinity.